Penerapan Program Desa Bersih Narkoba dalam Layanan Rehabilitasi berbasis Masyarakat - Xavia Rafailah; Alleyah Ufayroh (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The Drug Clean Village Program (Bersinar) is a program that implements advocacy and dissemination activities. Advocacy here is to provide understanding to the public about the adverse effects of narcotics abuse through outreach in the community. This activity was carried out by a team of Field Line officers as described above and also involved important figures as resource persons, such as the BNNK and the Police. The targets and objectives of this activity are all elements in the village, both for the village community and village officials. Continuing the Dissemination activity, this activity contains coaching and empowerment activities for the Village community. This activity is carried out by a team of Recovery Agents. The targets of this activity are victims of narcotics abuse who have attended community-based rehabilitation and/or recovery services, youth and families who have problems with drug use disorders in one of their members.